Innovating firms and aggregate innovation - Tor Jakob Klette; Samuel Kortum (University of Oslo, Department of Economics, 2002)
We develop a parsimonious model of innovating firms rich enough to confront firm-level evidence. It captures the dynamic behavior of individual heterogeneous firms, describes the evolution of an industry with simultaneous entry and exit, and delivers a general equilibrium model of technological change. While unifying the theoretical analysis of firms, industries, and the aggregate economy, the models yields insight into empirical work on innovating firms. It accounts for the persistence over time of firms' R & D investments, the concentration of R & D among incumbents firms, and the link between R & D and patenting . Furthermore, it explains why R & D as a fraction of revenues is strongly related to firm productivity yet largely unrelated to firm size or growth.
Keywords: L11; O31; 330; R&D; firm growth; productivity; market structure; endogeneous growth theory; birth and death processes; Innovation; Betriebliche Forschung; Unternehmenswachstum; Markteintritt; Allgemeines Gleichgewicht; Neue Wachstumstheorie; Theorie